Effects of aerobic training on serum paraoxonase activity and its relationship with PON1-192 phenotypes in women - Gulbin Rudarli Nalcakan; S. Rana Varol; Faruk Turgay; Mesut Nalcakan; M. Zeki Ozkol; S. Oguz Karamizrak (Elsevier, 2016)
Background: Paraoxonase 1 (PON1) is an antioxidant enzyme that protects high-density lipoprotein (HDL) and low-density lipoprotein against oxidation. Limited studies have addressed the influence of exercise on PON1 activity and its relationship with PON1 phenotypes. We investigated relationships between PON1-192 phenotypes, PON1 activity, aerobic exercise, and blood lipid and lipoprotein concentrations in middle-aged women. Methods: An exercise group (n = 50) engaging in regular aerobic exercise and a control group (n = 41) were selected from a subset of 300 Caucasian women that met the inclusion criteria. Serum PON1, salt-stimulated PON1 (SSPON1), and arylesterase (ARE) activities; cholesterol levels and ARE activities of total HDL and HDL subgroups (HDLs) (supernatants obtained by polyethylene glycol); and blood lipid and lipoprotein concentrations were determined by standardized enzymatic methods. PON1-192 QQ (low activity), QR (moderate activity), and RR (high activity) phenotype groups were defined using serum SSPON1/ARE activity ratios. The R-carries (RC) phenotype group consisted of the QR and RR groups combined. Results: All lipid and lipoprotein concentrations were greater in the exercise group than in the control group. Regardless of phenotype, no significant differences were observed between the exercise and control groups in terms of serum PON1, SSPON1, or ARE activity associated with HDLs (p > 0.05), whereas PON1 activities in QQ-phenotyped women in the exercise group were significantly higher than those in the control group (p < 0.01), but not the RC group. A statistically significant interaction between PON1 phenotypes (QQ and RC groups) and exercise (exercise and control groups) on PON1 activity was found. Conclusion: These results showed that a regular aerobic exercise program can improve PON1 activity depending on PON1-192 phenotype, but not on lipid and lipoprotein levels, in middle-aged Turkish women. Keywords: Aerobic exercise program, Arylesterase, Lipids, Lipoproteins, Paraoxonase, PON1-192 phenotype, Women